Use of Paediatric Xylometazoline Nasal Drop is not a Child’s Play in Hypertensive Patients on Bisoprolol: A Case Report - Bhalla, Hira; Gupta, Abhishek; Patel, Tejas (Current Drug Safety, 2021)
Background: Xylometazoline, a sympathomimetic agent, is considered safe in hypertensive patients as a relief measure for nasal congestion with intranasal application. Case Report: In the present case, a 58-year old male patient, having ischemic heart disease, controlled hypertension on telmisartan and bisoprolol, experienced hypertensive urgency in a span of two hours of intranasal administration of the paediatric formulation of xylometazoline. Conclusion: The interaction with bisoprolol should be kept in mind while using xylometazoline.
Keywords: Xylometazoline